The Socio-Economic Benefits of Community-based Mangrove Ecotourism in Lontar Village, Serang Regency - Encep Saefullah; Syamsul Hidayat; Fatari Fatari; Malik Fatoni; Nani Rohaeni (Jurnal Kawistara, 2023)
Ecotourism has been increasingly recognized as providing benefits not only in preserving the natural environment but can also improve the economy of local communities. To validate this assumption, the purpose of this study is to evaluate the implementation of Mangrove ecotourism in Lontar Village, Tirtayasa District, Serang Regency and its benefits to the community. The research method uses a qualitative descriptive method. The sample for this study was 70 respondents by asking questions using a questionnaire sheet in the form of Criteria and Indicators for Indonesian Ecotourism (KIEI) Year 2009. Data on potential came from field observations taken in the mangrove ecotourism area of Lontar Village. To verify ecotourism studies, the technique used is a formative evaluation of ongoing ecotourism activities with the application of KIEI. The results of this study indicate that based on the 5 criteria formanaging ecotourism according to the KIEI guidelines, the results of the implementation of conservation activities were 46.32% sufficient, participation 48.41% good, education and recreation 47.73% good, economy 45.19% sufficient. , and control of 43.91% less category. Based on the research results, tourists and the community strongly agree that the socioeconomicbenefits of community-based ecotourism management are 44.40%.